Zika virus: Global health challenge, threat and current situation. Issue 6 (16th February 2017) - Aziz, Hafsa; Zia, Aadarash; Anwer, Amania; Aziz, Muneeba; Fatima, Shazia; Faheem, Muhammad
Abstract : ZIKV has emerged as grave global health issue in the past few years. ZIKV was firstly isolated in 1947 from a rhesus sentinel monkey in the Zika forest in Uganda. It is usually transmitted by the bite of infected mosquitoes and infects skin fibroblasts, skin keratinocytes, etc. ZIKV until now was under reported because of its clinical similarity with the dengue and chikungunya. It is usually spread through the course of the sylvatic cycle. In this cycle, the virus or pathogen lifespan is spent between the wild animal and vectors. The intrinsic incubation period is not yet fully known but it is observed that the very first symptoms of ZIKV infection can appear or develop within 3–12 days of time period and usually subside within 7 days of time. There is a strong relationship between prenatal Zika virus infection and microcephaly; other serious brain anomalies to the infant or newborn are Guillain–Barré syndrome. To date no vaccines are available for ZIKV prevention hence only symptomatic treatment is recommended in infected patients. Usually ZIKV is detected by serologic (IgM ELISA), plaque reduction neutralization test (PRNT) along with in‐house" molecular techniques (RT‐PCR). ZIKV infection being imminent global health issue warrants strong protective measures to prevent it from becoming an epidemic. Early detection and prevention is the key to tackle this grave potential health hazard. J. Med. Virol. 89:943–951, 2017 . © 2017 Wiley Periodicals, Inc.